Direct visualisation of collateral ventilation in COPD with hyperpolarised gas MRI. Issue 7 (27th January 2012) - Marshall, Helen; Deppe, Martin H; Parra-Robles, Juan; Hillis, Susan; Billings, Catherine G; Rajaram, Smitha; Swift, Andrew; Miller, Sam R; Watson, Joanna H; Wolber, Jan; Lipson, David A; Lawson, Rod; et al.
Abstract : Background: Collateral ventilation has been proposed as a mechanism of compensation of respiratory function in obstructive lung diseases but observations of it in vivo are limited. The assessment of collateral ventilation with an imaging technique might help to gain insight into lung physiology and assist the planning of new bronchoscopic techniques for treating emphysema. Objective: To obtain images of delayed ventilation that might be related to collateral ventilation over the period of a single breath-hold in patients with chronic obstructive pulmonary disease (COPD). Methods: Time-resolved breath-hold hyperpolarised 3 He MRI was used to obtain images of the progressive influx of polarised gas into initially non-ventilated defects. Results: A time-series of images showed that 3 He moves into lung regions which were initially non-ventilated. Ventilation defects with delayed filling were observed in 8 of the 10 patients scanned. Conclusions: A method for direct imaging of delayed ventilation within a single breath-hold has been demonstrated in patients with COPD. Images of what is believed to be collateral ventilation and slow filling of peripheral airspaces due to increased flow resistance are presented. The technique provides 3D whole-lung coverage with sensitivity to regional information, and is non-invasive and non-ionising.